Heavy metals in Danggui (Angelica sinensis) consumed by postpartum mothers and its health risk - Ahmad Bustami, Normina; Yu, Bin Ho; Tan, Chung Keat; Aris, Ahmad Zaharin; Tan, Eugenie Sin Sing (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2020)
Introduction: Consumption of Chinese Herbal Medicine (CHMs) have escalated globally. They are preferred treatment for minor diseases or disorders. In Malaysia, CHMs are common home remedies during pregnancy and postpartum. Angelica sinensis (Danggui) is a staple CHMs during postpartum for purpose of nourishing blood and resolving stasis. Concerns are raised over possible heavy metals toxicity. Objective: This study aims to (i) determine Danggui consumption among postpartum mothers, (ii) quantify its heavy metals level, namely Lead (Pb), Cadmium (Cd), Arsenic (As) and Chromium (Cr) and (iii) determine health risks of Danggui consumption among mothers. Methods: A cross-sectional study involving 112 postpartum mothers was carried out in Kuala Lumpur. Danggui samples were collected from nine districts in Kuala Lumpur (Segambut, Seputeh, Cheras, Kepong, Bandar Tun Razak, Titiwangsa, Setiawangsa, Batu and Lembah Pantai). Heavy metals were extracted using microwave digester and analysed using Inductively coupled plasma mass spectrometry (ICPMS). Hazard Quotient (HQ) was used to determine non-carcinogenic health risks for herbal medicine consumption. Results: Danggui was consumed by 19.6% of mothers (n=22). Among them, incidence of jaundice was 63.6% and need for phototherapy was 40.9%. Heavy metals contaminations were found in the decreasing order of Cr > As > Pb > Cd with median (interquartile) of 3996.3 (2805.6) μg/ kg, 128.3 (56.7), 98.6 (99.1) and 37.0 (35.0) respectively. No non-carcinogenic health risks were found for all four metals. Conclusion: Alarming concentrations of heavy metals were quantified in Danggui warranting for further investigation to safeguard health of postpartum mothers.